Social class and infirmity. The role of social class over the life-course - Carin Lennartsson; Harpa Sif Eyjólfsdóttir; Roger Keller Celeste; Johan Fritzell (Elsevier, 2018)
In an aging society, it is important to promote the compression of poor health. To do so, we need to know more about how life-course trajectories influence late-life health and health inequalities. In this study, we used a life-course perspective to examine how health and health inequalities in late-midlife and in late-life are influenced by socioeconomic position at different stages of the life course. We used a representative sample of the Swedish population born between 1925 and 1934 derived from the Swedish Level of Living Survey (LNU) and the Swedish Panel Study of Living Conditions of the Oldest Old (SWEOLD) to investigate the impact of socioeconomic position during childhood (social class of origin) and of socioeconomic position in young adulthood (social class of entry) and late-midlife (social class of destination) on infirmity in late-midlife (age 60) and late-life (age 80). The results of structural equation modelling showed that poor social class of origin had no direct effect on late-midlife and late-life infirmity, but the overall indirect effect through chains of risks was significant. Thus, late-midlife and late-life health inequalities are the result of complex pathways through different social and material conditions that are unevenly distributed over the life course. Our findings suggest that policies that break the chain of disadvantage may help reduce health inequalities in late-midlife and in late-life. Keywords: Life course, Socioeconomic position, Late-life health